Additional cytosine inside mitochondrial C-tract D-loop as a progression risk factor in oral precancer cases - Rahul Pandey; Divya Mehrotra; Abbas Ali Mahdi; Rajiv Sarin; Pradnya Kowtal (Journal of Oral Biology and Craniofacial Research)
Introduction: Alterations inside Polycytosine tract (C-tract) of mitochondrial DNA (mtDNA) have been described in many different tumor types. The Poly-Cytosine region is located within the mtDNA D-loop region which acts as point of mitochondrial replication origin. A suggested pathogenesis is that it interferes with the replication process of mtDNA which in turn affects the mitochondrial functioning and generates disease. Methodology: 100 premalignant cases (50 leukoplakia & 50 oral submucous fibrosis) were selected and the mitochondrial DNA were isolated from the lesion tissues and from the blood samples. Polycytosine tract in mtDNA was sequenced by direct capillary sequencing. Results: 40 (25 leukoplakia & 15 oral submucous fibrosis) patients harbored lesions that displayed one additional cytosine after nucleotide thymidine (7CT6C) at nt position 316 in C-tract of mtDNA which were absent in corresponding mtDNA derived from blood samples. Conclusion: Our results show an additional cytosine in the mtDNA at polycytosine site in oral precancer cases. It is postulated that any increase/decrease in the number of cytosine residues in the Poly-Cytosine region may affect the rate of mtDNA replication by impairing the binding of polymerase and other transacting factors. By promoting mitochondrial genomic instability, it may have a central role in the dysregulation of mtDNA functioning, for example alterations in energy metabolism that may promote tumor development. We, therefore, report and propose that this alteration may represent the early development of oral cancer. Further studies with large number of samples are needed in to confirm the role of such mutation in carcinogenesis.